Load Perturbation Facilitates Interpersonal Error Compensation in a Dyadic Force Production Task. Issue 1 (2nd January 2019) - Masumoto, Junya; Inui, Nobuyuki
ABSTRACT: The present study tested the hypothesis that a load perturbation facilitates interpersonal compensation for force error. Ten groups performed both control and perturbation conditions. In the control condition, a target discrete peak force was the sum of 10% of the maximum voluntary contraction produced by two participants. In the perturbation condition, two cooperative participants a and b produced the same target force as the control condition, and the force produced by a non-cooperative participant c increased or decreased the total forces produced by participants a and b. The load perturbation facilitated interpersonal compensation for force error but negatively affected performance during joint action. The participants further learned to improve the error compensation over experimental blocks in the perturbation condition.